Quantization-based simulation of switched mode power supplies. (April 2015) - Migoni, Gustavo; Kofman, Ernesto; Bergero, Federico; Fernández, Joaquín
In this article we study the performance of quantized state system algorithms in the simulation of switched mode power supplies. Under realistic modeling assumptions, these models are stiff and exhibit frequent discontinuities, making them difficult to simulate with classic solvers. However, there are linearly implicit quantized state system methods that can efficiently handle these types of systems, providing faster and more accurate results. In order to corroborate these features, we first built the models corresponding to the different topologies of switched mode power supplies, and then analyzed the resulting equation structures in order to establish whether they can be efficiently simulated by linearly implicit quantized state system algorithms. Finally, we compared the simulation performance of linearly implicit quantized state systems with the widely used DASSL solver. The results showed that the linearly implicit quantized state systems were 3–200 times faster and noticeably more accurate than the differential algebraic system solver.